Literacy Culture and Its Effectiveness in Improving Indonesian Students’ Writing Skills - Lestari, Sri Indah; Kusumawati, Tri Indah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to examine the effectiveness of literacy culture in improving students’ composing ability in Indonesian subjects in secondary schools with a qualitative approach to case studies. The subject of this study is a group of students in one of the secondary schools who have applied literacy activities regularly in learning Indonesian. Data was collected through classroom observations, in-depth interviews, and analysis of student writing products. The findings of the study show that the application of literacy culture in the classroom is able to improve students’ composing skills in terms of organizing ideas, creative expression, and using more appropriate and varied language. In addition, teacher support factors and a conducive school environment also accelerate the development of students’ writing skills. Literacy culture can play a significant role in improving students’ composing skills, although its application requires careful planning and consistency in its implementation.